Proceedings of the 16th International ACM SIGACCESS Conference on Computers &Amp; Accessibility - ASSETS '14 2014
DOI: 10.1145/2661334.2661373
|View full text |Cite
|
Sign up to set email alerts
|

A computer-based method to improve the spelling of children with dyslexia

Abstract: In this paper we present a method which aims to improve the spelling of children with dyslexia through playful and targeted exercises. In contrast to previous approaches, our method does not use correct words or positive examples to follow, but presents the child a misspelled word as an exercise to solve. We created these training exercises on the basis of the linguistic knowledge extracted from the errors found in texts written by children with dyslexia. To test the effectiveness of this method in Spanish, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…Other related research within the field of human–computer interaction (HCI) may be applied to explore these issues further, and there is a substantial amount of work to build on; for instance, guidelines on web accessibility and web readability (Miniukovich, Angeli, Sulpizio, & Venuti, ; Santana, Oliveira, Almeida, Cec, & Baranauskas, ; Venturini & Gena, ), using games to improve spelling skills (Rello, Bayarri, Otal, & Pielot, ), and including people with dyslexia in the development teams (González, ). Based on the existing research, it seems purposeful to explore these issues further, since spelling correction and string‐matching methods might reduce the impact of spelling errors in an information searching context.…”
Section: Cognitive Impairmentsmentioning
confidence: 99%
“…Other related research within the field of human–computer interaction (HCI) may be applied to explore these issues further, and there is a substantial amount of work to build on; for instance, guidelines on web accessibility and web readability (Miniukovich, Angeli, Sulpizio, & Venuti, ; Santana, Oliveira, Almeida, Cec, & Baranauskas, ; Venturini & Gena, ), using games to improve spelling skills (Rello, Bayarri, Otal, & Pielot, ), and including people with dyslexia in the development teams (González, ). Based on the existing research, it seems purposeful to explore these issues further, since spelling correction and string‐matching methods might reduce the impact of spelling errors in an information searching context.…”
Section: Cognitive Impairmentsmentioning
confidence: 99%
“…Dytective uses linguistic and attentional exercises designed to distinguish populations with and without dyslexia. Empirical analyses show that errors made by people with dyslexia are different from the errors made by people without dyslexia [29] and, have been successfully used for dyslexia intervention [24]. Hence, the criteria for the linguistic exercises were built on the basis of an analysis of an existing resource of errors made by people with dyslexia [22].…”
Section: Errors As Source Of Knowledgementioning
confidence: 99%
“…During eight weeks, the authors carried out a within-subject experiment with 48 children from 6 to 11 years old. Children who played Dyseggxia for four weeks in a row had significantly less writing errors in the tests than after playing the control condition for the same time [12]. Our game differs from previous work in being the first tool for German based on written dyslexic errors.…”
Section: Related Workmentioning
confidence: 68%
“…In the case of dyslexia, exercises on paper introduce an added difficulty for some students due to the fact that dysgraphia 2 is comorbid with dyslexia [7]. More recently, it was shown that computer games are a convenient medium to provide exercises in an engaging way to significantly improve the reading performance [10,11] and the spelling performance [12] of children with dyslexia. These methods cannot simply be extended to other languages because manifestations of dyslexia depend on the different orthographies of the languages [13].…”
Section: Introductionmentioning
confidence: 99%